Effects of probiotics on haematology and biochemical parameters in mice (Bangladesh Veterinarian, 2013)
Probiotic organisms are live microorganisms thought to be beneficial to the host. To know the effect of probiotic supplemented food on haemato-biochemical parameters in mice, a total of 20 two-month-old Swiss Albino mice were randomly divided into four equal groups. Group A was control, fed commercial mouse pellets, and others were treated with 5 g (group B), 10 g (group C) and 20 g (group D) probiotics (curd), respectively, in mouse pellets for 45 days. Total erythrocyte count and haemoglobin concentration were significantly (P